Estrogen deficiency and periodontal condition in rats: a radiographic and macroscopic study - Anbinder, Ana Lia; Prado, Marcela De Almeida [UNESP]; Spalding, Marianne; Balducci, Ivan [UNESP]; Carvalho, Yasmin Rodarte; Rocha, Rosilene Fernandes Da (Fundação Odontológica de Ribeirão Preto, 2006)
The purpose of this study was to evaluate the impact of ovariectomy-induced estrogen deficiency as a risk factor of periodontal disease in rats. Forty 90-day old female rats were either ovariectomized (OVX; n=20) or sham operated (SHAM; n=20). After 30 days, periodontitis was induced by placement of a cotton ligature around the upper second molars of 10 OVX and 10 SHAM animals. All animals were sacrificed 5 weeks later. Body weight was assessed before all surgical procedures. The left hemimaxillas were removed and the percentage of periodontal bone support was determined radiographically and buccal alveolar bone loss was determined macroscopically using an image-analysis software. Furcation involvement was also evaluated. Data were analyzed statistically by ANOVA at 5% significance level. Within the evaluated period, the ovariectomized rats gained more weight than the sham-operated animals (p<0.001). The animals in which periodontitis was induced had less bone support, greater alveolar bone loss and furcation involvement than those without ligature (p<0.001). However, there was no difference between ovariectomized and sham-operated animals (p>0.05). Based on the findings of this study, estrogen deficiency could not be considered as a risk factor for periodontal disease.

O objetivo deste trabalho foi avaliar a influência da ausência de hormônios ovarianos induzida por ovariectomia como fator de risco para a doença periodontal em ratas. Quarenta ratas com idade de 90 dias foram submetidas a ovariectomia (OVX; n=20) ou cirurgia simulada (sham) (SHAM; n=20). Após 30 dias, ligaduras de algodão foram colocadas ao redor dos segundos molares superiores de 10 animais OVX e 10 animais SHAM. Cinco semanas após, todos os animais foram sacrificados. As ratas foram pesadas antes de todos os procedimentos cirúrgicos. As hemimaxilas esquerdas foram removidas e determinaram-se a porcentagem de suporte ósseo, através de radiografias, e a área de perda óssea alveolar, macroscopicamente, após maceração, com auxílio de programa computacional, além do grau de envolvimento de furca. Os dados foram submetidos à análise estatística por meio de ANOVA com nível de significância de 5%. No período avaliado, as ratas ovariectomizadas apresentaram maior ganho de peso que aquelas submetidas à cirurgia simulada (sham) (p<0.001). As ratas em que foi induzida periodontite apresentaram suporte ósseo estatisticamente menor e maior perda óssea alveolar e envolvimento de furca que as demais (p<0.001). Porém, não foram encontradas diferenças significantes entre os animais ovariectomizados e não-ovariectomizados (p>0.05). Com bases nos achados deste estudo, a deficiência de hormônios ovarianos não pôde ser considerada como fator de risco para a doença periodontal.
Keywords: periodontal disease; osteoporosis; ovariectomy